SURGICAL METHODS IN THE COMPLEX TREATMENT OF ORTHOPEDIC PATIENTS IN PERMANENT BITE - V. І. Kutsevliak; О. V. Liubchenko; Yu. H. Danilova; V.V. Starikov (Ukrainian Medical Stomatological Academy, 2016)
The article presents the experimental and clinical substantiation of new solutions in orthodontics improving the efficiency and reducing the time of orthodontic treatment of patients in permanent occlusion combined method, by applying corticotomy and devices of its own design, building on mini implants, with the use of physical factors and medicines. To solve this problem, you must fulfill three conditions: 1. Create a fixed support relative to which the movement of the teeth; 2. The creation of orthodontic appliances with fixing on a fixed support; 3. Create a path for bone directional movement of the tooth. The clinical and experimental studies have been conducted. Total number - 187 teenagers and adults aged 16-21 years. Analysis of the structure of dentoalveolar anomalies was carried out by classification Angle and D. • Kalvelis. From the bite pathology often observed prognathic bite (23.5%) - youth - 10.7%, adults - 22.3%; overbite - 18.7%: teens - 10.7%, adults - 17.6%. Outdoor and cross-bite was 8.5%, while the teenagers - 5.8%. Adults with open bite were 9.4%, and with the cross - 7.05%. Creating a fixed support. When planning the biomechanical aspects of orthodontic treatment it is important to consider not only the force to move the teeth, but also unwanted movement of teeth, arising under the influence of applied forces. Orthodontic implants entered into clinical practice for the controlled movement of teeth as fixed skeletal support that is more predictable and secure. We have developed a system of orthodontic mini implants, which includes several sizes for use in different parts of the alveolar processes of the upper and lower jaws (patent of Ukraine №39559, №40998, №40999, №41257, №88590, №90607). Carrying out experimental and clinical studies have to prove complex design features mini implants, which provide the following advantages: - the presence of two diameters of the intra osseous mini implants - cortical - 2.4 mm and a sponge - 1.2 mm enables a differentiated redistribute mainly on cortical bone; - thread pitch intra osseous portion is 1 mm, which also reduces the stress in the cortical and cancellous bone in particular layer; - individually costed mini implants sizes allow to install it in any part of the alveolar process. Creation of orthodontic appliances with fixation on mini implants was made possible by the developed "anchor system" (patent of Ukraine №90607), which is a metal plate made individually mounted on both sides in the orthodontic mini implants. On the plate, there are hooks for fixing the load-bearing elements (patent of Ukraine №40998). This allows you to move the teeth group orthodontic appliances (patent of Ukraine №99168, №66862, №107918) developed on the principles of the "anchor of the system" (patent of Ukraine №99168, №66862, №107918). To create a path for directional movement in the tooth bone experiments were conducted on rabbits. The experiments consisted of playing a single and a double fault with a diameter of 2 mm - compactotomy - in the body of the mandible region and further studying the characteristics of reparative osteogenesis and remodeling processes in a maternal bone in response to a traumatic injury, the extent of its recompactication. For this purpose, 7 and 14 days after the defect when reproducing experimental material evaluation were selected. These terms include 3 and 4 stage of reparative osteogenesis - the formation and reorganization of tissue structures. For objectification of experimental data, morphometric analysis of tissues were carried out, filling the wound defect, and evaluation of vascular density and resorption cavities compact bone near the defect and in the area between the adjacent defects. The findings suggest that when playing the double defect of rabbit s jaw, the process of reparative osteogenesis maintains the general orientation, but reclaimed on the 14th day different degrees of tissue maturity. Delay the differentiation of tissues. The defect was 2 times more osteoid reduced area occupied by cancellous bone and lamellar (1.1 and 2.4 times, respectively). Intensity resorptive processes in the compact bone adjacent to the defect, was 2.1 times higher than in the adjacent sections. Two or more defect compact bone resorption create targeted at a distance of 5 mm. resorption areas, merging with each other, create targeted resorption line that you can move a tooth directed. On the basis of summarizing the results of the study it was composed of orthodontic treatment regimen of patients in permanent dentition: - fixation of orthodontic apparatus on mini implants; - laser phoresis with Lydasum 10 days before the operation, 10 procedures; - surgery - compactotomy, compactosteotomy, extractions, etc .; - activation of the unit on the 14th day from the beginning compactotomy; - magnetotherapy - after the end of the active period 20 treatments; - retention. The active period of comprehensive orthodontic treatment in permanent dentition was 46.3 weeks, while Apparatus treatment in a similar group of patients was 66.3 weeks, 20 weeks more.